Association of High Mobility Group Box-Protein 1 and Platelet Microparticles in Patients After Hematopoietic Stem Cell Transplantation - Shosaku Nomura MD; Jun Ichikawa MD; Toshiki Shimizu MD; Yoshihisa Ishiura MD; Masaya Okada MD; Kazuyoshi Ishii MD; Tomoki Ito MD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Thrombotic complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT) significantly impact transplant outcomes. We focused on high mobility group box-protein (HMGB)1, one causative agent of thrombotic lesions in allo-HSCT, and investigated its association with platelets. We statistically analyzed available data from 172 patients with hematopoietic malignancies receiving allo-HSCT. A significant enhancement of monocyte-chemotactant protein-1, HMGB1, and platelet-derived microparticle (PDMP) levels was observed at day 0 after transplantation as compared to pre-transplantation. Multivariate analysis of the association among HMGB1 and 16 factors on day 0 revealed a significant correlation of HMGB1 levels with thrombin–antithrombin complex, interleukin-6, and PDMPs. High mobility group box-protein 1-induced procoagulant platelet induction and PDMP generation were performed in vitro using healthy platelets. High mobility group box-protein 1-induced PDMP generation was suppressed by toll-like receptor inhibitors and recombinant thrombomodulin. These results suggest that HMGB1 contributes to platelet activation in patients after allo-HSCT and is associated with PDMP-related thrombotic complications.